Thidiazuron-induced morphogenesis in tamarind seedlings - Mehta, Urmil J.; Sahasrabudhe, N.; Hazra, Sulekha (In Vitro Cellular & Developmental Biology-Plant, 2005)
Germination of tamarind seeds in medium containing thidiazuron (TDZ) resulted in induction of nodular protrusions in and around the cotyledonary node meristem. The structures developed radially in well-defined circles and subsequently spread towards the cotyledonary bridge and also in the proximal part of the hypocotyl. The structures developed into shoots on transfer to medium devoid of growth regulators. Histological studies revealed that the protrusions initiated from the nodal meristem and extended to the non-meristematic region between the two meristems and also in the proximal part of the hypocotyl in seedlings germinated in 9.08 mu M TDZ. Newly formed cell layers and less-differentiated meristematic protrusions were also seen. With the increase in the distance from the meristem, the buds were less differentiated; in the proximal part of the hypocotyl only the multiple layers of meristematic cells were noted. With extension of the period of incubation, the TDZ-induced meristematic activity extended laterally in circles towards the neighboring region. The radial spread of the meristematic activity from the center of the nodal meristem was also evident at 18.16 mu M TDZ. From the pattern of the morphogenic development and the histological studies it may be hypothesized that in tamarind, TDZ influences the existing meristems specifically. Subsequently de novo organogenesis is triggered in the neighboring cells.
Keywords: Caulogenesis; Histology; morphogenesis; protrusions; thidiazuron